Identification and first insights into the structure and biosynthesis of chitin from the freshwater sponge Spongilla lacustris - Ehrlich, Hermann; Kaluzhnaya, Oksana V.; Brunner, Eike; Tsurkan, Mikhail V.; Ereskovsky, Alexander; Ilan, Micha; Tabachnick, Konstantin R.; Bazhenov, Vasilii V.; Paasch, Silvia; Kammer, Martin; Born, Rene; Stelling, Allison; et al. (Journal of Structural Biology, 2013)
This work demonstrates that chitin is an important structural component within the skeletal fibers of the freshwater sponge Spongilla lacustris. Using a variety of analytical techniques (13C solid state NMR, FT-IR, Raman, NEXAFS, ESI-MS, Morgan-Elson assay and Calcofluor White Staining); we show that this sponge chitin is much closer to α-chitin, known to be present in other animals, than to β-chitin. Genetic analysis confirmed the presence of chitin synthases, which are described for the first time in a sponge. The presence of chitin in both marine (demosponges and hexactinellids) and freshwater sponges indicates that this important structural biopolymer was already present in their common ancestor. © 2013 Elsevier Inc.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Bioanalytics; Chitin; Chitin synthase; Skeleton; Sponges